The Use of Media in the Field of Da’wah: Between Reality and Prospects - Aminul Hoque, Muhammad (Journal of Humanities & Social Sciences, 2025)
Media is considered one of the most influential tools in shaping societal awareness and guiding communities in the modern era. Its utilization in the field of Islamic da’wah has become an urgent necessity to keep pace with the rapid changes in the world of communication and knowledge. This study aims to examine the current use of media in Islamic da’wah, identify the main challenges faced by preachers and Islamic institutions in this domain, and clarify the requirements for activating these media in a manner consistent with Islamic values and responsive to contemporary needs. The study adopts a descriptive-analytical approach by reviewing previous studies and observing contemporary models of da’wah media practices. The findings indicate that the current state of da’wah media suffers from weak strategic planning, a shortage of qualified media professionals, scattered efforts among institutions, in addition to intellectual and cultural challenges emerging from globalized media. The study recommends the need to train specialized personnel who combine Islamic jurisprudence with media expertise, establish modern media platforms, and develop clear policies to leverage digital media for widely disseminating Islamic da’wah.